Speech text of virtual innovation competition 2023 (VIC 2023) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
It is a great pleasure for me to welcome everyone to the Virtual Innovation Competition 2023 (VIC 2023). I am thrilled to be given the honour to address all guests and participants and officiate this remarkable international event. Allow me to extend my greatest appreciation to DIGIT360 Sdn Bhd - a startup company under UiTM, Digital Information Interest Group (DIGIT), and the College of Computing, Informatics, and Media, UiTM Kelantan Branch for hosting VIC 2023.